Project management demystified - Kemp, Sid. 4 0 16; 5 (New York : McGraw-Hill, 2004)
Presents a guide to project management, including information on transforming ideas into projects, turning to-do lists into action plans, bringing teams together, keeping a project under budget, and gaining skills that can be used again and again.
Includes bibliographical references and index.
Young Adult.
Keywords: 2 -- 0; 6; Project management. -- 20; 20; 2